Intervención fisioterapéutica en neuropatía femoral post-histerectomía. - Del Pozo Gavilánez, María Fernanda (2024)
Post-hysterectomy femoral neuropathy (FN) is a condition that can occur after a gynecologic procedure resulting in the side effect of nerve compression due to inadequate placement of fixed or self-retaining retractors and prolonged lithotomy, which causes weakness in hip flexion and knee extension movements. Nerve conduction studies such as an electromyogram or ultrasound are used for diagnosis (Romo Rodriguez et al., 2014). The present research is a literature review of documentary type with the aim of analyzing the effects of physiotherapeutic intervention in patients with femoral neuropathy associated with hysterectomy, through the collection and bibliographic analysis of scientific articles to demonstrate which is the most effective post-surgical therapeutic approach. A compilation of scientific articles and bibliographic reviews was carried out in databases such as: Pubmed, PEDro, SCOPUS, ResearchGate, Springer, Cochrane Library. Initially, 136 articles were collected, of which 35 were used after evaluation using the PEDro scale with a score greater than or equal to 6. To verify the impact of the articles collected, the SJR (SCImago Journal Rank) scale was applied. By means of the systematic review, improvements in the patients have been evidenced, after the application of physiotherapeutic treatment, accompanied by gymnastics and pharmacology, which allows reducing the patients' symptomatology and controlling their return to daily life activities. After the analysis of articles, favorable changes were evidenced in terms of muscle weakness and the inability to complete standardized biomechanical movements of the hip and knee, in addition to recovering the sensitivity of the leg.